2010
DOI: 10.1016/j.cell.2010.06.035
|View full text |Cite
|
Sign up to set email alerts
|

PNPASE Regulates RNA Import into Mitochondria

Abstract: SUMMARY RNA import into mammalian mitochondria is considered essential for replication, transcription, and translation of the mitochondrial genome but the pathway(s) and factors that control this import are poorly understood. Previously, we localized polynucleotide phosphorylase (PNPASE), a 3′ → 5′ exoribonuclease and poly-A polymerase, in the mitochondrial intermembrane space, a location lacking resident RNAs. Here, we show a new role for PNPASE in regulating the import of nuclear-encoded RNAs into the mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
405
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(442 citation statements)
references
References 42 publications
(69 reference statements)
14
405
2
5
Order By: Relevance
“…To date, several groups have reported successful examples of mitochondrial RNA delivery [29][30][31], since the fact that the mitochondrion possesses endogenous RNA imported via an RNA signal tag system in these studies [32,33]. Moreover, it has been reported that allotropic expression in the nucleus, followed by the transfer of a signal tag fused protein to the mitochondria appears promising [11].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several groups have reported successful examples of mitochondrial RNA delivery [29][30][31], since the fact that the mitochondrion possesses endogenous RNA imported via an RNA signal tag system in these studies [32,33]. Moreover, it has been reported that allotropic expression in the nucleus, followed by the transfer of a signal tag fused protein to the mitochondria appears promising [11].…”
Section: Discussionmentioning
confidence: 99%
“…First, two recent, independent studies have shown the presence of the RNA subunit of both P and MRP RNases in the matrix of human mitochondria (97,99). Although the corresponding protein subunits have not been found in this organelle, from the protein composition already described, it can be inferred that their function could be performed by a different set of proteins.…”
Section: Exceptions To the Rule: Uncommon Sources For Rnase P/mrp Funmentioning
confidence: 99%
“…This is indeed true in the case of mitochondrial RNase P from yeast, a RNP complex where one protein component is unrelated to the nuclear protein components (100). Moreover, there is evidence that the RNAs imported to the human mitochondria by PNPase are involved, at least to some degree, with tRNA processing (97).…”
Section: Exceptions To the Rule: Uncommon Sources For Rnase P/mrp Funmentioning
confidence: 99%
“…RNase P typically functions as an RNA-protein complex, comprised of one conserved RNA and a varying number of protein subunits, depending on the domain of life: one in Bacteria, at least four in Archaea, and nine or more in the eukaryotic nucleus (4,5). A precedent in which the RNA component is missing entirely is found in human and Arabidopsis organellar RNase P (6, 7), although a recent study suggests the possible coexistence of protein-only and RNA-protein-based RNase P complexes in human mitochondria (8).…”
mentioning
confidence: 99%